The ParentingWell Practice Approach: Adaptation of Let’s Talk About Children for Parents With Mental Illness in Adult Mental Health Services in the United States - Nicholson, Joanne; Heyman, Miriam; English, Kelly; Biebel, Kathleen (Frontiers in Psychiatry, 2022)
Background: Despite the importance of family and parent-focused practice, there has been a dearth of research on interventions for parents with mental illness. This paper describes the process and outcome of adapting an evidence-based intervention, Let’s Talk about Children (LTC), in the context of adult mental health services in Massachusetts, USA. Methods: Specific objectives included: (1) to specify the core components, functions, and principles of LTC essential to adapting the intervention (i.e., program theory), (2) to consider contextual factors related to the new setting; (3) to pre-test the adapted materials with diverse practitioners; and (4) to compile the program model and materials (i.e., the practice profile) for use by adult mental health service providers in Massachusetts. The Adaptation Team included individuals with expertise in psychiatric rehabilitation and clinical care, policymaking, program development and research, and parents. Activities occurred between 2015 to 2019 and included: (1) consulting with experts to specify the core elements and theory behind the selected intervention (i.e., with the LTC purveyor and international experts); (2) consulting with key stakeholders for input regarding the Massachusetts target population and context to inform adaptations (i.e., individual and group key informant interview sessions); (3) pretesting the initial adapted materials (i.e., training and coaching sessions with adult mental health practitioners); and (4) using feedback to refine and compile the final intervention manual (i.e., the ParentingWell Practice Profile). Participants reflected diverse, oftentimes multiple roles and perspectives, including those of parents with mental illness, adult children, and family members. Results: ParentingWell is practitioner- and setting-agnostic, addresses parenting across the lifespan, fits into the routine workflow, and builds on practitioners’ existing skills. Eight themes emerged, which were translated into four core elements (engage, explore, plan, access and advocate) consistent with Self-Determination Theory and four underlying principles (trauma-informed, strengths-based, family-focused, culturally-sensitive) in keeping with the LTC model. The ParentingWell Practice Profile operationalizes each core element and addresses the underlying principles. Conclusions: ParentingWell makes talking about parenting and family experiences a routine part of the therapeutic conversation with adults with mental illness. Future research will test the adaptation, implementation, and impact of ParentingWell.